A wireless temperature monitoring systems - Noorismaawi, Yusop (2005)
These days,the use of computer laboratory in higher learning institution has become a compulsory element for the student in order to finish and settle down the assignment given by lectures.Unfortunately, computer laboratory do not have any temperature warning sign. This can cause an emergency like being fire in the room because the people did not notice of what is happening.In this project which is focus in Fakulti Sistem Komputer Dan Kejuruteraan Perisian (FSKKP) computer laboratory.The temperature of the computer laboratory can be detected and will be displayed in liquid crystal display (LCD) all the time and also will be displayed in the system.Testing is done on the device attach to the computer (system) by using the wireless technology. The overheat current temperature data transmitted to the system by using the radio frequency (RF) from the device to the system.It's mean the current temperature from the device will transmitted to the system by using radio frequency (FR).Operation RF is 433.92 mega hertz (MHZ).The type of hardware used is 16F877 microcontroller that will be main controller of this project.In the device also has the buzzer that will be ringing when the current temperature as hot.Meanwhile in the system, it will be displayed the temperature when the temperatureis hot.Hopefully,with this project, its can help to ensure that the current laboratory temperature always in normal condition.